Enhancing the photocatalytic activity under visible light of chromium doped TiO2 thin film prepared by sol-gel method - Phung, Nguyen Thai Hang (H. : ĐHQGHN, 2017)
The pure TiO2 and Cr doped TiO2 (TiO2:Cr) photocatalyst thin films were prepared by solgel method using chromium (III) chloride and tetra butyl orthotitanate with doping levels of 1 to 7 at. %. The structure of TiO2:Cr thin films was determined through XRD diffraction. Surface morphology and grain size were estimated by SEM images. Doped concentrations of chromium in the films were determined by EDX spectrum. The visible light photocatalytic activity of the samples was quantified by measuring the rate of degradation of methylene blue (MB) under visible light irradiation. The results show that all films possess the anatase structures and the crystalsizes of them are about 18 nm. The 5 at.% Cr doped TiO2 film shows the highest visible light photocatalytic activity. It can nearly decompose about 50% MB solution and get super wet state after 150 minutes under visible light irradiation. The TiO2:Cr films have the better photocatalytic activity under visible light than that of pure TiO2 films.